Electrical safety in the workplace - Neyra Vela, Frank John (2020)
Electricity is the driving force behind progress in all industry and globally, the most widely-used form of energy currently used; however, if it is not used properly and workers do not have the necessary training, there is potential for it to cause damage. This research studies the main hazards regarding electricity: electric arc and electric shock. For this reason, an electrical safety methodology that consists in recognizing the hazards associated with the use of electricity to take preventive actions to avoid hazards that cause injury or death is applied. After performing an analysis on electric arc and shock, results contributed to the prevention of accidents in the workplace, per the NFPA 70E and IEEE 1584-2002 standards.